Insight into clinical, laboratory, and GIT ultrasound diagnostic findings of cystic fibrosis in pediatrics - Dina H. Hamed; Rania SM. Ibrahim; Marwa A. Hakim; Mona Mohsen (SpringerOpen, 2022)
Abstract Background Cystic fibrosis (CF) is a multisystem disorder. Gastrointestinal tract (GIT) involvement presently requires medical attention, and this improves the survival rate of patients with CF. GIT imaging has an essential role in the early detection of GIT affection. This study aimed to quantify the abdominal symptoms and their relationship to clinical findings, abdominal ultrasound scoring system, and laboratory parameters, correlating GIT manifestation with ultrasound diagnostic findings. Methods This was a cross-sectional study that included 60 patients diagnosed with CF based on clinical manifestations and confirmed by a positive sweat chloride test ≥ 60 mmol/L and/or genetic analysis (CFTR gene mutation; a copy from each parent) in the CF clinic in the Children's Hospital, in a period of 12 months. Results Recurrent abdominal pain (RAP) was the most common GIT manifestation, followed by abdominal distension and steatorrhea. Ultrasonography (US) showed that the most frequent findings were pancreatic lipomatosis in 16 patients (26.7%), the next common finding was heterogeneous coarse hepatic parenchyma in 14 patients (23.3%), while the least finding was the thickened bowel walls in 2 patients (3.3%). Abdominal US scoring revealed that the highest burden of GIT symptoms was clearly associated with pancreatic lipomatosis and liver steatosis with the highest score (6/7) (p = 0.048), while bowel wall thickness (BWT) had the lowest score (3/7) (Table 4). Conclusion This study reveals that abdominal US is a non-invasive investigation that helps in the early detection of GIT involvement in CF. RAP is a common GIT manifestation and may reflect a major pathology. Moreover, a significant relationship was detected between RAP and pancreatic cystosis and lipomatosis. Therefore, the study also highlights the importance of US as a routine non-invasive follow-up tool for patients with CF and suggests close monitoring of patients with CF by abdominal US performed every 6 to 12 months.